By Using Model Shift and Improving The Walking Facilities: A Case Study In Kuala Lumpur, Malaysia - Ali A Mohammed (Institute of Advanced Engineering and Science, 2014)
The recent increase in privately owned vehicles has caused numerous problems: traffic congestions, unnecessary fuel lost and global warming are only few of these problems. This study will try to understand people’s behavior and modal choice and try to sway them to means of public transportation. A survey of mode choice between cars users in a neighborhood in Kuala Lumpur was conducted. A total of 25 surveys were collected over the course of a month. Among data collected were demographic details such as age, gender, educational level and travel behavior. The data was processed by SPSS software to determine which factors encourages and discourages using private, public transportation or walking. The study highlighted four models travel time reduction, travel cost reduction, and increase the parking charges and improves the walking facility. The sensitivity analysis results show that the main attraction that might switch private car users is travel time and improving the walking facility. The consequences of these would be less traffic on the roads contributing to less pollution and greater safety.